(untitled) (Talenta Conference Series: Science and Technology (ST), 2018)
The quadratic assigment problem (QAP) has remainedone of the great challenges in combinatorial optimization. In this paper I propose two programs, the MATLAB program for solving QAP, and the MATLAB program for checking objective value, if we input an arbitrary permutation, matrix flow and matrix distance. The first program using combination methods that combines random point strategy, forward exchange strategy , and backward exchange strategy. I‘ve tried my program to solve Esc 16b, Esc 16c and Esc 16h from QAPLIB (A Quadratic Assignment Problem Library). In the 500th iteration optimal value reached and I‘ve found the other assignment for problem instances Esc 16b, Esc 16c, and Esc 16h.